1998
DOI: 10.1071/a97067
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea in wheat-based cropping systems of northern New South Wales. II. Influence on biomass, grain yield, and crown rot in the following wheat crop

Abstract: Rotational effects of chickpea, an important N2-fixing pulse legume of the northern grains region, on subsequent wheat require quantification of the contribution of the legume to soil N and the N status of the wheat, and of suppression of soil and stubble-borne pathogens, such as crown rot (Fusarium graminearum Schwabe Group 1). Results from selected treatments of 10 experiments in northern New South Wales in which chickpea and wheat in one season were followed by wheat in following seasons indicated generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In another investigation, crown root rot of wheat caused by Fusarium graminearum was reduced and wheat yield increased by a chickpea-wheat versus wheat-wheat rotation. The mean incidence of crown rot was 12 % for chickpea-wheat rotation, compared with 30 % infection in wheat-wheat system (Felton et al 1998 ) . The effect of crop rotation including canola, lupine, medic, medic-clover mixture on the incidence of wheat crown root rot disease was investigated.…”
Section: Crop Rotationmentioning
confidence: 97%
“…In another investigation, crown root rot of wheat caused by Fusarium graminearum was reduced and wheat yield increased by a chickpea-wheat versus wheat-wheat rotation. The mean incidence of crown rot was 12 % for chickpea-wheat rotation, compared with 30 % infection in wheat-wheat system (Felton et al 1998 ) . The effect of crop rotation including canola, lupine, medic, medic-clover mixture on the incidence of wheat crown root rot disease was investigated.…”
Section: Crop Rotationmentioning
confidence: 97%
“…Mean monthly temperatures were tested because of the reported association between temperature and infection (Wildermuth and McNamara 1994). Felton et al (1998) reported that soil moisture at sowing was related to incidence of disease at the end of the season. Soil moisture was not measured in most crops at Moree, so the soil moisture model in the DYMEX software package (Maywald et al 1999) was used to estimate stored moisture.…”
Section: Regression Analysismentioning
confidence: 99%
“…Crown rot is an example of a polyetic disease (Zadoks 1999) in which the epidemic develops over successive years and the incidence of disease in 1 year is influenced by the incidence in the previous year. Some of the published work on crown rot has failed to take this into account, and comparisons between management treatments have been made in 1 year without considering the previous history of the disease (Felton et al 1998). Developing a full-scale predictive system for crown rot will require an understanding of the mathematical nature of polyetic changes in disease incidence.…”
mentioning
confidence: 98%
“…Rotation using resistant crops or pastures is another recommended practice for reducing inoculum of the crown rot fungus (Burgess et al, 1996, Felton et al, 1998. In northern New…”
Section: Pre-and Postharvest Practicesmentioning
confidence: 99%
“…South Wales, Felton et al (1998) compared crown rot disease incidence of wheat, which followed chickpea rotation, and wheat which followed wheat. The authors reported reduced incidence of crown rot in wheat after chickpea, compared with wheat after wheat, which supports a large number of observations and studies that show the beneficial effects of a break crop.…”
Section: Pre-and Postharvest Practicesmentioning
confidence: 99%